Strengthening the success rate of suprapubic aspiration in infants by integrating point-of-care ultrasonography guidance: A parallel-randomized clinical trial. - Sadroddin Mahdipour; Seyedeh Nastaran Seyed Saadat; Hamidreza Badeli; Afagh Hassanzadeh Rad (PLoS ONE)
Background Urinary tract infection (UTI) is a common disease in childhood. A sterile collection of urine samples using suprapubic aspiration (SPA) and bladder catheterization (BC) is helpful for rapid and accurate diagnosis of UTI in infants. With the advent of point-of-care ultrasound (POCUS), the use of ultrasound by non-radiologists at the patient's bedside, great advancement has been noticed in various medical fields. Considering the importance and advantages of using POCUS in the physical examination and guiding procedures, the authors aimed to compare urine sampling's success rate by SPA, BC, and POCUS guided SPA (POCUS-SPA) in infants performed by three pediatricians. Materials and methods This study is a randomized clinical trial conducted on 114 neonates and infants with suspected UTI admitted to 17-Shahrivar children's hospital from April 2017 to September 2019. Neonates and infants were randomly assigned to three groups of BC, SPA, and POCUS-SPA. The primary outcome was the success of sampling defined by obtaining 1cc of urine in each method. The secondary outcome was assessing the pain level. Results Results showed that the POCUS-SPA had the highest success rate in urine sampling, and a statistically significant relation was noted among the three groups (P = 0.0001). From 38 patients in each group, 37 patients of POCUS-SPA (97.4%), 34 patients of BC (89.5%), and 23 patients of SPA (60.5%) had a successful sampling. Most of the patients in all three groups experienced severe pain. Conclusions In the current study, results showed that the POCUS-SPA significantly increased the success rate of urine sampling and most of the patients in all three groups had severe pain. Based on the shortage of access to radiologists in emergency setups, it seems that the POCUS-SPA by the pediatricians can be one of the most appropriate and applicable diagnostic methods in infants with UTI.